Analysis of the determinants of entrepreneurship of young rural in Morocco - AMMARI, Siham (Revue Internationale des Sciences de Gestion, 2022)
In order to better understand the debate on rural, it is necessary to examine more closely the determinants of entrepreneurial intentions declared by rural youth and to assess their entrepreneurial spirit. With this in mind, a survey was conducted in the rural communes of the Meknes prefecture with 90 young graduates, including 70 young men and 20 young women with an average age of 33 years. These young people were approached through a questionnaire and direct observations. The data collected was processed through a descriptive analysis and the Multiple Correspondence Factorial Analysis (MCA). The analysis brings to light that the reasons for the creation of enterprises by rural youth are among the seven modalities associated with the motivations, as well as the financial support of the projects carried by the youth remains a source of capital financing for 24% of the young entrepreneurs surveyed. And finally, the public mechanisms put in place are struggling to position themselves as really effective measures to support entrepreneurial initiatives in rural areas.